2011
DOI: 10.5334/ijic.678
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Care in New Zealand

Abstract: Background: New Zealand's health system has long been seen as providing highly fragmented, poorly co-ordinated services to service users. A continuing policy challenge has been how to reduce such fragmentation and achieve more 'integrated' care, that is, 'co-ordinated' care that provides a 'smooth and continuous' transition between services, and a 'seamless' journey as service users receive health, support, and social welfare services from a range of health and other professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(104 citation statements)
references
References 18 publications
1
103
0
Order By: Relevance
“…Other high bed number countries include Austria (intercept 1350) and Germany (1320), hence while the average for developed countries is a helpful benchmark it is important to realize that countries with high levels of integrated care such as Sweden (intercept 800), Singapore and New Zealand (790) operate with around 40% fewer beds that the developed countries average (Figure ). However, such levels of bed provision are only achieved after many years of effort enabled by government policy . Australia is generally not considered to have a highly integrated health care service, and hence bed provision lies near to the International average for developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…Other high bed number countries include Austria (intercept 1350) and Germany (1320), hence while the average for developed countries is a helpful benchmark it is important to realize that countries with high levels of integrated care such as Sweden (intercept 800), Singapore and New Zealand (790) operate with around 40% fewer beds that the developed countries average (Figure ). However, such levels of bed provision are only achieved after many years of effort enabled by government policy . Australia is generally not considered to have a highly integrated health care service, and hence bed provision lies near to the International average for developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…Gillies et al (1993) described integrated care as the coordination of activities between different functioning units for the purpose of providing efficient health services to patients. From a public health perspective, primary care is the hub of many integrated healthcare systems where it has been considered as the means to achieving integration (Albrecht 1998;Cumming 2011;Robinson & Casalino 1996;Van Lerberghe 2008). Valentijn et al (2013) considered that primary care, defined in terms of accessibility of services, continuity of care, availability of services and health service coordination, is the establishment of integrated care.…”
Section: Tie Level (Tie Strength)mentioning
confidence: 99%
“…By 2011 an independent analysis concluded that the act had succeeded in integrating planning and funding functions and "assisted in focusing attention on the roles that an enhanced primary care service might play in better supporting integrated care." 12 Although that study cautioned that insufficient progress had been made in service delivery, in 2013 the UK health think tank the King's Fund reported how Canterbury District Health Board, in the South Island, had shown that, with clinical leadership, "it is possible to provide better care for patients, reduce demand on the hospital, and flatten or reduce elements of the demand curve across health and social care by improved integration," concluding that what was happening was "transformational." 13 New Zealand has shown that health legislation that focuses on competition and market forces is unsuccessful and unpopular and that "careful crafting of governance, contracting, funding and information sharing" can achieve important benefits by avoiding competition and fragmentation.…”
Section: Observations Cross Party Support For More Integrated Carementioning
confidence: 99%